Peran Komite dalam Pengembangan Madrasah - Djafrin Bagu; Moh. Hasbi (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
This paper aims to describe the role of school committees in efforts to improve the quality of education. The research method used is descriptive qualitative, with in-depth interview data collection techniques. Data analysis was carried out using the Miles and Huberman qualitative data analysis technique. The results showed that the role of the school committee was to improve quality, equity, and efficiency in the management of education in the education unit. Both in pre-school education, school education and out-of-school education. The dysfunction of the school committee's duties as a follow-up to community aspirations does not affect the decline in the quality of education. This is because the educational device as a social system is autopoietic which can renew the dysfunction in one or several educational subsystems. Participation is expanded in various aspects, both facilities, infrastructure, and cooperation with stakeholders.